"Painted Blind": Dressing and Addressing "Colorblind" Ideology in a South African and an American Dream - Gordon, Colette (Shakespeare bulletin, 2021)
"What exactly does it mean for race not to matter?" Lisa M. Anderson’s 2006 essay delivers a profound and far-reaching answer: that, in the "colorblind" dreams of American life or of the theater, the disappearance of race signifies merely the disappearing trick of whiteness. Theater engages what Patricia Hill Collins terms "controlling images," and the power of these shaping fantasies means that we keep, and must keep, answering the question, in shifting contexts. This essay examines two productions of A Midsummer Night’s Dream produced in the same year, one in North America (Shakespeare Theatre Company, Washington DC), one in South Africa, (Artscape, Cape Town), with particular attention to the casting and presentation of the lovers. In 2012, Ethan McSweeney cast a white Hermia and Lysander and a black Helena and Demetrius for his DC production, dividing the lovers into two (hierarchical) classes occupying different worlds: a creative class (privileged, rebellious, liberal, and white) and a consumerist class (aspirational, fawning, conservative, and black). In this arrangement, with casting and design working together to "tell a story," interracial love was staged as mismatching, a swerving from the natural bias—notably, both after and before the love potion is administered. Fred Abrahamse’s South African production of the same year told a very different story, favoring interracial love and a playful awareness of sameness and difference, and showing the lovers not worlds apart but part of the same world. However, here too class and economics (and race) matter.